Indonesian Language: The Challenges and its Teaching - Ekasiswanto, Rudi (Allure Journal, 2024)
Teaching Indonesian as a curriculum compulsory subject (MKWK) in university implies some challenges, considering the teaching is intended for students who have yet to study language theoretically and conceptually formally. This research is reflectively aimed at describing teaching challenges and possibilities. Methodologically, this study involved the researcher as an Indonesian language teacher in a university using a reflective-introspective way to gather data based on his experience. The results of this study are as follows: The students have various scientific backgrounds that are substantially and culturally different. Conditionally, they do not study Indonesian historically, culturally, theoretically, and methodologically. This implies that the orientation of teaching Indonesian needs to be formulated. Indonesian as MKWK is taught functionally for language purposes in higher education. Language as a signifying medium becomes a verbal or oral communication tool to disseminate knowledge. Thus, the teaching materials are also adjusted elementary to the scientific background of each student. This allows the establishment of relations between Indonesian as a subject and other disciplines. Thus, awareness of this aspect of teaching makes it possible to place Indonesians not as "additional" but as "significant" learning in universities.